2005
DOI: 10.1021/jp0511754
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Hydration Dynamics in Melittin Folding and Aggregation:  Helix Formation and Tetramer Self-Assembly

Abstract: Melittin, an amphipathic peptide from honeybee venom, consists of 26 amino acid residues and adopts different conformations from a random coil, to an alpha-helix, and to a self-assembled tetramer under certain aqueous environments. We report here our systematic studies of the hydration dynamics in these conformations using single intrinsic tryptophan (W19) as a molecular probe. With femtosecond resolution, we observed the solvation dynamics occurring in 0.62 and 14.7 ps in a random-coiled primary structure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
82
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 64 publications
14
82
1
Order By: Relevance
“…The obtained total dynamic Stokes shift is 1,725 cm Ϫ1 , and the emission maximum s (0) at t ϭ 0 is Ϸ320 nm, consistent with previous observations (43) and recent MD simulations (44). The possible contribution of vibrational relaxation is negligible (24), and thus the observed total Stokes shift is predominantly from the local solvation. Using…”
Section: Figsupporting
confidence: 90%
See 1 more Smart Citation
“…The obtained total dynamic Stokes shift is 1,725 cm Ϫ1 , and the emission maximum s (0) at t ϭ 0 is Ϸ320 nm, consistent with previous observations (43) and recent MD simulations (44). The possible contribution of vibrational relaxation is negligible (24), and thus the observed total Stokes shift is predominantly from the local solvation. Using…”
Section: Figsupporting
confidence: 90%
“…Using intrinsic tryptophan as a local optical probe (22, 23), we have recently characterized hydration dynamics for a series of proteins in different structures, conformations and complexes with DNA and ligands, and at the surface, interface and binding pocket (24)(25)(26)(27). Using the single tryptophan, W31, we can determine time scales of water motions at the active site.…”
mentioning
confidence: 99%
“…These processes represent the dynamic exchange of hydration layer water with outside bulk water via thermal fluctuations. Femtosecond-resolved spectroscopic studies of protein solvation (19)(20)(21)(22)(23)(24)(25)(26) recently have shown the dynamics of surface hydration on picosecond time scales with a biphasic distribution. We attributed the first ultrafast solvation to water local relaxation and the second longer-time dynamics to coupled water-protein fluctuations (25,27).…”
mentioning
confidence: 99%
“…Typically, extrinsic dye molecules or synthetic amino acids were used as local optical probes to label function sites, and the local relaxations were observed, ranging from femtoseconds to nanoseconds (5,(12)(13)(14). Such labeling of bulky dye molecules usually induces significant local perturbations, and direct characterization with intrinsic chromophores in proteins eliminates those interferences and reveals intact environment responses (4,7,(15)(16)(17)(18)(19)(20)(21), as recently examined in green fluorescence proteins (21). We have recently studied a series of flavoproteins using intrinsic flavin molecule as the optical probe (10,22,23) and especially found the important functional role of local solvation in photolyase (10).…”
mentioning
confidence: 99%